ANALISIS PERBANDINGAN HARGA SAHAM DAN VOLUME PERDAGANGAN SAHAM PT UNILEVER INDONESIA TBK SEBELUM DAN SETELAH MUI MENGELUARKAN FATWA MUI NO. 83 TAHUN 2023 - Jannati , Nur Baiti; Mutmainah , Kurniawati; Guspul, Ahmad; Hartiyah, Sri; Akbar, Muhamad Asif Maulana (E-Jurnal Akuntansi TSM, 2025)
Fatwa No. 83 of 2023 issued by the Indonesian Ulema Council (MUI), which urges Muslims to avoid products affiliated with Israel, has generated negative public sentiment, including toward companies such as PT Unilever Indonesia Tbk. This study aims to examine the differences in stock price and trading volume of PT Unilever Indonesia Tbk before and after the issuance of the fatwa. A quantitative approach was employed using an event study methodology, with the Wilcoxon Signed Rank Test applied to data from 100 days before and after the event. The results reveal a significant difference in stock price, but not in trading volume. These findings suggest that socially driven religious information can act as a negative signal to investors, leading to a decline in stock prices, although not necessarily accompanied by changes in trading activity. The implications highlight the importance for companies to recognize the potential impact of socio-religious issues on market perception and encourage further research on market reactions to non-economic information.